Dampak shock kebijakan moneter terhadap ketimpangan pendapatan di Indonesia - meylinda sulfiana putri; Wasiaturrahma Wasiaturrahma (Trunojoyo University of Madura, 2019)
Households have different sources of income, and the heterogeneity of income will make the interest rates from monetary policy have a different impact because the effect of redistribution so that it will eventually cause the differences in income distribution. The channel of monetary policy redistribution shows how the transmission mechanism of monetary policy affect income distribution and eventually have an impact on income inequality. This study aims to find out and analyze the impact of monetary policy on income inequality in Indonesia in 1995Q1 – 2017Q4 and examine one of the channels of the transmission mechanism that is income composition channel. The analytical method used is Vector Error Correction Model, this is based on the existence of a cointegration relationship in the analysis model used. The results of the study show that contractionary monetary policy by raising interest rates can increase income inequality both in the short term and long term and on the contrary expansive monetary policy can reduce income inequality. Expansive monetary policy can encourage economic activity, reduce unemployment and increase income especially for low-income households, so that this condition can produce a better income distribution.